The relationship between limb length and flexibility with the speed of martial arts side kicks - Andito Andito; Panuwun Joko Nurahyo; Kusnandar Kusnandar; Didik Rilastiyo Budi; Arfin Deri Listiandi; Neva Widanita; Ayu Rizky Febriani; Heryanto Heryanto (Indonesian Journal of Research in Physical Education, Sport, and Health, 2023)
The problem delivered in this study is that some fighters are easily caught when performing side kicks, need help attacking rivals with a higher posture, and need to reach the optimal point when performing splits. This study aims to determine the correlation between leg length and flexibility with the speed of side kicks in martial arts. This quantitative research defines the correlation between the independent and dependent variables. This research uses sampling of 30 fighters by utilizing purposive sampling. The research instrument for limb length uses a rolling meter and flexibility using a side split test, while a statistical test uses multiple correlations. The results showed that (1) there was no significant correlation between leg length and sidekick speed with a sig. of 0.621; (2) There is a significant correlation between flexibility with sidekick speed and the sig value of 0.002;(3) There is a significant correlation between leg length and flexibility with sidekick speed, with an r-value of 0.007. This study concludes that anthropometric components are needed to do side kicks quickly and well in martial arts, especially leg length and physical condition aspects of flexibility.